2003
DOI: 10.1007/s11661-003-1000-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the atomic ordering processes in Fe3Al intermetallics by the monte carlo simulation method combined with electronic theory of alloys

Abstract: The evolution of atomic ordering processes in Fe 3 Al has been modeled by the Monte Carlo (MC) simulation method combined with the electronic theory of alloys in pseudopotential approximation. The magnitude of atomic ordering energies of atomic pairs in the Fe 3 Al system has been calculated by means of electronic theory in pseudopotential approximation up to sixth coordination spheres and subsequently used as input data for MC simulation for more detailed analysis for the first time. The Bragg-Williams long-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…The results of this simulation study showed that such a combination of methods can be successfully applied for qualitative and/or semi-quantitative analysis of energetical and structural characteristics of the atomic ordering processes in Fe 3 Al-type intermetallics. In this present study, therefore, it is of interest to confirm the validity of the approach proposed by Mekhrabov and Akdeniz [5] for the description of the atomic ordering processes in the L1 2 -type ordered intermetallics such as Ni 3 Al.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…The results of this simulation study showed that such a combination of methods can be successfully applied for qualitative and/or semi-quantitative analysis of energetical and structural characteristics of the atomic ordering processes in Fe 3 Al-type intermetallics. In this present study, therefore, it is of interest to confirm the validity of the approach proposed by Mekhrabov and Akdeniz [5] for the description of the atomic ordering processes in the L1 2 -type ordered intermetallics such as Ni 3 Al.…”
Section: Introductionsupporting
confidence: 64%
“…In the present study, our intention is not to perform solely MC simulation using a large number of atoms for the complete description of atomic ordering processes; it is rather to confirm the validity of the new approach proposed in our previous study [5] for the evaluation of atomic ordering and order-disorder transition phenomena in Ni 3 Al intermetallics with the L1 2 -type ordered FCC superstructure. A three-dimensional 15 × 15 × 15 lattice with L1 2type unit cell having 13 500 lattice sites has been defined for MC simulation.…”
Section: Modelling and Simulation Proceduresmentioning
confidence: 68%
See 2 more Smart Citations
“…On the other hand, ordered intermetallics constitute a unique class of materials that form long-range ordered (LRO) crystal structure below a critical temperature that is generally referred to as the critical order-disorder phase transition temperature [15,16]. The interest in such materials emanate from their attractive properties such as high strength, stiffness, stability and oxidation resistance ideal for structural applications at elevated temperatures [15]. The thermodynamic stability of these compounds relates to their high bond strength brought about by ordering.…”
Section: Introductionmentioning
confidence: 99%